The Influence of Accounting Information Systems, Product Innovation, and Product Quality on the Financial Performance of MSMEs in Batam City - Rini Haryanti Ndruru; Viola Syukrina E. Janrosl (International Journal of Social Science and Humanity, 2025)
This study aims to analyze the influence of accounting information systems, product innovation, and produkct quality on the financial performance of MSMEs in Batam City. MSMEs play a crucial role in regional economic growth but face challengses such as weak financial management and low product competitiveness. This research employs a quantitative approach focused on collecting and analyzing numerical data. Data were obtained through questionnaires distributed via Google Forms to 100 MSME actors in Batam City, selected using Slovin’s formula and simple random sampling. The collected data were processed using SPSS 25 and measured with a Likert scale. The results indicate that accounting information systems, product innovation, and product quality significantly affect MSMEs financial performance, both partially and simultaneously. These findings suggest that effective financial record-keeping systems, continuous product innovation, and improved product quality are vital factors to enhance the financial performance and competitiveness of MSMEs amid increasingly competitive market conditions.